Hydraulic bearing puller - Abu Bakar, Nor Hidayah; Mohd Zaini, Mohd Zairin Aiza; Mohd Fuzi, Muhamad Firdaus; Hassan, Mohd Fahrul; Radzuan, Muhammad Dinie Al-Syafiq; Hussein, Muhammad Hafeez (Penerbit UTHM, 2017)
A bearing puller tool is an essential repair aid when working on an engine or machine that has pressure-set bearings in its mechanisms. Without the tool, repair of bad bearings would be difficult and prone to a high risk of damage to the shaft or casing block of gearbox and engine. It is designed as a tool to make the removal and installation of bearings simple and efficient, bearing pullers often resemble a pair of scissors. In some cases, the configuration of the puller will allow the extraction of both gears and bearings, including those that are connected with a series of shafts within the mechanism. Different sizes of bearing pullers make it possible to use the device on everything from a pair of skates to complicated industrial machinery. ‘Hydraulic Bearing Puller' is one of the products that have been modified from the original product in the market. Extensive studies have been conducted on service centers to implement this product. Most workers remove the bearing from the shaft (shaft) a way tap so that it can be removed. Apart from that they also use the 'bearing puller' common but with high cost. From the original product, we have made modifications to equipment for easy used by employees.